Digestive Characteristics of Hericium erinaceus Polysaccharides and Their Positive Effects on Fecal Microbiota of Male and Female Volunteers During in vitro Fermentation - Tian, Baoming; Geng, Yan; Xu, Tianrui; Zou, Xianguo; Mao, Rongliang; Pi, Xionge; Wu, Weicheng; Huang, Liangshui; Yang, Kai; Zeng, Xiaoxiong; Sun, Peilong (Frontiers in Nutrition, 2022)
Hericium erinaceus polysaccharides (HEPs) have attracted widespread attention in regulating gut microbiota (GM). To investigate digestibility and fermentation of HEPs and their effects on GM composition, three polysaccharide fractions, namely, HEP-30, HEP-50, and HEP-70, were fractionally precipitated with 30%, 50%, and 70% ethanol concentrations (v/v) from hot water-soluble extracts of Hericium erinaceus, respectively. Three kinds of prepared HEPs were structurally characterized and simulated gastrointestinal digestion, and their effects on human fecal microbiota fermentations of male and female and short-chain fatty acid (SCFA) production in vitro were clarified. Under digestive conditions simulating saliva, stomach, and small intestine, HEPs were not significantly influenced and safely reached the distal intestine. After 24 h of in vitro fermentation, the content of SCFAs was significantly enhanced (p < 0.05), and the retention rates of total and reducing sugars and pH value were significantly decreased (p < 0.05). Thus, HEPs could be utilized by GM, especially HEP-50, and enhanced the relative abundance of SCFA-producing bacteria, e.g., Bifidobacterium, Faecalibacterium, Blautia, Butyricicoccus, and Lactobacillus. Furthermore, HEPs reduced the relative abundances of opportunistic pathogenic bacteria, e.g., Escherichia-Shigella, Klebsiella, and Enterobacter. This study suggests that gradual ethanol precipitation is available for the preparation of polysaccharides from Hericium erinaceus, and the extracted polysaccharide could be developed as functional foods with great development value.